1999
DOI: 10.3109/08916939908993852
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Restriction of Autoreactive T Cell Responses in Pemphigus Vulgaris: Review of the Literature and Potential Applications for the Development of a Specific Immunotherapy

Abstract: Pemphigus vulgaris (PV) is a life-threatening autoimmune bullous disease of the skin and mucous membranes which requires immunosuppressive therapy, most commonly a combination of glucocorticoids and additional immunosuppressive agents. Since the side effects of long-term immunosuppressive therapy contribute to the poor prognosis of this disorder, there is considerable interest in a more specific treatment of this severe skin disease. PV may serve as a model disease for the development of a specific immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 61 publications
8
31
0
Order By: Relevance
“…This observation clearly demonstrates that both autoreactive Th1 and Th2 cells are present in PV, although at different frequencies during the course of the disease. These findings extend previous studies that derived both Dsg-reactive Th1 and Th2 clones from the peripheral blood of patients with PV (11)(12)(13)(14)23). Their detection, however, requires assay systems of adequate sensitivity, as demonstrated herein compared with ELISPOT analysis (16).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This observation clearly demonstrates that both autoreactive Th1 and Th2 cells are present in PV, although at different frequencies during the course of the disease. These findings extend previous studies that derived both Dsg-reactive Th1 and Th2 clones from the peripheral blood of patients with PV (11)(12)(13)(14)23). Their detection, however, requires assay systems of adequate sensitivity, as demonstrated herein compared with ELISPOT analysis (16).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, a recent study from our laboratory showed in healthy donors that Dsg3 peptides may also be presented by HLA class II alleles that share distinct peptide binding motifs with the PV-associated HLA-DRB1*0402 or DQB1*0503 alleles. Dsg3-reactive T cell clones from a Dsg3-reactive healthy donor were restricted by HLA-DRB1*1102 that shares the negatively charged residues, asparagic acid and glutamic acid, at positions DR␤70 and ␤71 with the PVassociated allele, HLA-DRB1*0402, and by HLA-DQB1*0301 that shares asparagic acid at position B57 with the PV-associated HLA-DQB1*0503 (14,23). The importance of these distinct peptide binding motifs of the aforementioned HLA class II alleles is supported by the identification of Dsg3 peptides, such as peptide DG 190 -204 , that carry a positive charge at the P4 pocket that may be critical for binding to the negatively charged P4 pockets of DRB1*0402 (DR␤70 and -71) and DQB1*0503 (DQ␤57) (17,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, PBMC from four DRB1*0402 PV patients were only stimulated by two of these Dsg3 peptides, aa 190 -204 and aa 206 -220 (19). Dsg3 peptide aa 190 -204 is homologous to peptide DG3(189-205) of the current study, the later Dsg3 peptide (aa 206 -220) is homologous to peptide DG3(205-221) of this study and peptide aa 210 -226 of the aforementioned study (30) (Table IV). Thus, the findings of the present study clearly extend the previous observations of Wucherpfennig and coworkers by demonstrating that autoaggressive T cells of PV patients do indeed recognize a limited set of Dsg3 peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Using long-term CD4 + T cell clones, our group demonstrated that the majority of HLA-DRB1*04:02-positive PV patients showed a proliferative T cell response to these HLA-DRB1*04:02-binding Dsg3 T cell peptides (Table III) (8,9,42). Specifically, all of the identified Dsg3 epitopes share common anchor residues at relative positions 1, 4, and 6, which were previously identified to be potential anchor motifs for DRB1*04:02 and carry a positive charge at position 4, which is critical for binding to the negatively charged P4 pocket of DRB1*04:02 (Table III) (6,42).…”
Section: Discussionmentioning
confidence: 99%